EFFECT OF RETURN ON INVESTMENT (ROI) ON STOCK PRICE ( Study At Pt Astra International 2013-2018 ) - Erwin Erwin; Oyon Suharyono (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2020)
Study This goal is to ascertain how return on investment affects the share price of PT Astra International. Time frame for the study: this covers the years 2013–2018. population studied This is a mining company that is listed on IDX. Purposive sampling is used in the election sample. In the years 2008 to 2010, there were up to 31 firms miningyang listed on the IDX. utilized data analysis Simple regression analytical techniques are used to test the hypothesis.According to a results study, the results mark significance of 0.935 acquired by results processing statistics is larger than the criteria significance (0.05). The regression model is therefore not significant. Therefore, the linearity criterion is satisfied by linear regression. The R2 result is 0.002 which indicates that the variability variable dependent may be described by the variability variable independent by 0.2% while the remaining 99.8% is explained by other factors not included in the regression model.